Nek Pung Dance E-Module Development Study: Practicality and Effectiveness in Learning - Wahid, Abdul; Novianti, Ulfah; Nugroho, Muhammad Toto; Sanchez, Joje Mar P (Journal of Elementary Educational Research, 2025)
Abstract This study aims to develop a local wisdom-based e-module for fourth-grade elementary students by integrating the Nek Pung dance, a traditional art from Tebo Regency, Jambi Province. The dance reflects cultural values such as gratitude, resilience, and appreciation of life, which are increasingly unfamiliar to younger generations. Integrating this cultural heritage into learning is essential for both educational quality and cultural preservation. The research employed a Research and Development (R&D) method using the ADDIE model: analysis, design, development, implementation, and evaluation. In the development stage, the e-module was validated by two experts. The material aspect scored 3.6 and 3.5, the media aspect 3.7 and 3.3, and the language aspect 3.7 and 3.6, all falling within the “valid” to “very valid” category. Practicality testing by three expert practitioners resulted in total scores of 42, 42, and 43, with an average practicality level categorized as “very practical.” In a small group trial with five students, the e-module received average ratings between 3.5 and 3.7, indicating strong usability. These findings suggest that the e-module is valid, practical, and effective in supporting learning and enhancing students' appreciation of local culture. This product demonstrates that integrating local wisdom in digital learning media is a meaningful strategy for education and cultural sustainability.